The Case of a Zebra That Was Misdiagnosed as a Horse: Pulmonary Tumor Thrombotic Microangiopathy, a New Paraneoplastic Syndrome, Mimicking PD-1-Induced Pneumonitis - Corey A. Carter; Robert Browning; Bryan T. Oronsky; Jan J. Scicinski; Christina Brzezniak (Case Reports in Oncology, 2016)
A case report of a 47-year-old woman with triple-negative breast cancer on a clinical trial called PRIMETIME (NCT02518958) who received the anti-PD-1 inhibitor nivolumab and the experimental anticancer agent RRx-001 is presented. Although initially diagnosed and treated for anti-PD-1-induced pneumonitis, clinical and radiological abnormalities triggered further investigation, leading to the diagnosis of pulmonary tumor thrombotic microangiopathy (PTTM). This example highlights the importance of exercising due diligence in determining immune-related adverse events and suggests that PD-1-induced pneumonitis should be a diagnosis of exclusion rather than a diagnosis by default. A case history and review of the literature are presented for PTTM, which we propose to define as a paraneoplastic syndrome.